2D integral formulae and equations for thermoelectroelastic bimaterial with thermally insulated interface - Pasternak, Ia. M.; Pasternak, R. M.; Sulym, H. T (Publishing House of Lviv Polytechnic National University, 2014)
The paper presents a complex variable approach for obtaining of the integral formulae and integral equations for plane thermoelectroelasticity of an anisotropic bimaterial with thermally insulated interface. Obtained relations do not contain domain integrals and incorporate only physical boundary functions such as temperature, heat flux, extended displacement and traction, which are the main advances of these relations. У роботi на основi методiв теорiї функцiї комплексної змiнної запропоновано прямий пiдхiд до побудови iнтегральних формул та рiвнянь плоскої термоелектропружностi для анiзотропного бiматерiалу з теплоiзольованою межею подiлу. Отриманi спiввiдношення не мiстять iнтегралiв по областi та залежать лише вiд фiзично значимих крайових функцiй, таких як температура, тепловий потiк, розширенi перемiщення та напруження, що є основними перевагами цих спiввiдношень.
Двовимiрнi iнтегральнi формули та рiвняння для термоелектропружного бiматерiалу iз теплоiзольованою межею подiлу
Keywords: thermoelectroelastic; anisotropic; bimaterial; integral formulae; термоелектропружний; анiзотропний; бiматерiал; iнтегральнi формули